2022
DOI: 10.1186/s12939-022-01681-w
|View full text |Cite
|
Sign up to set email alerts
|

Neutrality, conflict, and structural determinants of health in a Jerusalem emergency department

Abstract: Background Medical neutrality is a normative arrangement that differentiates a zone of medical treatment disconnected from the field of politics. While medical neutrality aims to ensure impartial healthcare for all and to shield the healthcare personnel from political demands, it can also divert attention away from conflicts and their effects on health inequity. This article analyzes how healthcare professionals understand and negotiate the depoliticized space of the emergency department (ED) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…However, the misjudgment was more prominent due to the poor specificity of the score and the unclear grading of MEWS. 6 This study explored the value of PRISMA-7, qSOFA, ESI, and CFS and their combination in predicting 28-day mortality risk in elderly patients in the emergency department. It confirmed that the sensitivity and specificity of different assessment systems were significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the misjudgment was more prominent due to the poor specificity of the score and the unclear grading of MEWS. 6 This study explored the value of PRISMA-7, qSOFA, ESI, and CFS and their combination in predicting 28-day mortality risk in elderly patients in the emergency department. It confirmed that the sensitivity and specificity of different assessment systems were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“… 4 At the same time, the emergency department is also one of the departments with a relatively high incidence of medical disputes, especially among the elderly and dead patients. 5 , 6 Therefore, it is essential to find an effective assessment method or scoring system for the early detection of high-risk elderly emergency patients.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the classification was similar; in the few instances where the classification differed, a discussion to resolve differences ensued. As described in Orr et al (2023), we subsequently identified connections between the initial categories, refined them, and combined similar categories. We finalized six core categories that comprised the meaningful thematic clusters around which we organized the findings (Corbin and Strauss 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Cultural competency improves providers’ communication and increases patient satisfaction, compliance, and healthcare access (Betancourt et al 2002; Campinha-Bacote 2002; Schuster, Elroy, and Rosen 2018). In the past decade, the needs and challenges of ultra-Orthodox people in Israel have been increasingly acknowledged in the framework of culturally competent healthcare (Freund, Cohen, and Azaiza 2019; Genut et al 2022; Orr et al 2023). Yet, the needs and challenges of religious disaffiliates have been completely ignored in this framework.…”
Section: Conclusion Implications Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation